Junior High School Students Having Been Confident to Speak English Well - Tarmizi Rasul; Ahmad Nasikin (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The data showed that 90% of the students at both Jakarta and Depok Junior High Schools could not speak English. There were 90% of Jakarta 253 State Junior High School unconfident to speak English. There were some problems. Two of them were the materials and method used. The objective of this study was to show that the new method called Oral Questioning Guidance in L1 (OQIGIL) was really effective to develop the students’ English-speaking skill especially at Jakarta 253 State Junior High School compared to the conventional ones. The finding of this study showed that The level of significance (?) = 0,05 , t table by testing two sides dk = n - 1= 36 – 1 = 35, by using table t was obtained t table score =2,029. It was obviously, t count t table ( 5,9 2,029 ). So, research hypothesis is accepted.